Fine mapping of the qHTB1-1QTL, which confers heat tolerance at the booting stage, using an Oryza rufipogon Griff. introgression line - Cao, Zhibin; Li, Yao; Tang, Huiwu; Zeng, Bohong; Tang, Xiuying; Long, Qizhang; Wu, Xiaofeng; Cai, Yaohui; Yuan, Linfeng; Wan, Jianlin (Theoretical and applied genetics, 2020)
Key message The qHTB1 - 1 QTL, controlling heat tolerance at the booting stage in rice, was fine mapped to a 47.1 kb region containing eight candidate genes. Two positional candidate genes showed significant changes in expression levels under heat stress. High-temperature stress at the booting stage has the potential to significantly limit rice production. An interspecific advanced backcrossed population between the Oryza sativa L. cultivar R53 and the wild Oryza rufipogon Griff accession HHT4 was used as the source material to develop a set of chromosome segment introgression lines to elucidate the genetic mechanism of the qHTB1 - 1 QTL in heat tolerance. A single-chromosome-segment introgression line, IL01-15, was used to develop secondary populations for the mapping of qHTB1 - 1 on chromosome 1 for heat tolerance at the booting stage. Using the BC 5 F 2 , BC 5 F 3 , and BC 5 F 4 populations, we first confirmed qHTB1 - 1 and validated the phenotypic effect. The qHTB1 - 1 QTL explained 13.1%, 16.9%, and 17.8% of the phenotypic variance observed in the BC 5 F 2 , BC 5 F 3 , and BC 5 F 4 generations, respectively. Using homozygous recombinants screened from larger BC 6 F 2 and BC 6 F 3 populations, qHTB1 - 1 was fine mapped within a 47.1 kb region between markers RM11633 and RM11642. Eight putative predicted genes were annotated in the region, and six genes were predicted to encode expressed proteins. The expression patterns of these six genes demonstrated that LOC_Os01g53160 and LOC_Os01g53220 were highly induced by heat stress in IL01-15 compared to R53. Sequence comparison of the gene-coding regions of LOC_Os01g53160 and LOC_Os01g53220 between R53 and IL01-15 revealed one synonymous and two nonsynonymous SNPs in exons, respectively. Our results provide a basis for identifying the genes underlying qHTB1 - 1 and indicate that markers linked to the qHTB1 - 1 locus can be used to improve the heat tolerance of rice at the booting stage by marker-assisted selection.